Comparative study of the determinants of wasted and stunted preschool children in Ternate, Cavite. - Diaz, Juanita H.
This study examines the factors that determine the nutritional status of preschool children in Ternate, Cavite. Data on factors related to family size, maternal education, nutrition knowledge and practices, and socioeconomic status were gathered using the questionnaire-interview method among mothers and analyzed to predict nutritional status. The prevalence of malnutrition among 0-6 year old children was computed using the Waterlow's 4-fold classification of nutritional status. Wasting was determined using weight for height index and compared with the 50th percentile of the National Center for Health Statistics (NCHS) Standard while stunting was assessed using height for age classification and compared with Jayme's Height and Weight Standards for Filipinos. Results showed that most of the subjects were normal (72.7 ), while the lowest percentage (4.3 ) were both wasted and stunted. There were more stunted (12.7 ) than wasted (10.3 ) children in the study. Wasted children were those whose heights were equal to or less than the cut-off point of 85 of the standard weight for height. Stunting occured when the cut-off level was reached or was lower than 90 of the standard height for age. Family size, education of the mother, nutrition knowledge and practices, and socioeconomic status were adequate predictors of nutritional status. However, only nutrition practices, family size and socioeconomic status were the best predictors as suggested by the magnitude of their R2 values. T-test results showed no significant difference among the observed characteristics between these 2 groups of malnourished children except for socioeconomic status. Chi-square test results found no association between factors like type of occupation of the father and the type of lactrine with nutritional status. Comparison of the determinants of wasting and stunting gave no significant effect on the 5 predictor variables. However, wasting was more affected by the said independent variables as indicated by their obtained R which was 23. On the other hand R2 for stunting was only 2 . Research results therefore emphasize the need to consider other factors that may affect stunting and to recourse to a longitudinal study for better evaluation of the factors affecting these 2 malnourished groups and for ample time to follow through the subjects.